If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(3x + 3) = 34 + 8x Reorder the terms: -6(3 + 3x) = 34 + 8x (3 * -6 + 3x * -6) = 34 + 8x (-18 + -18x) = 34 + 8x Solving -18 + -18x = 34 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -18 + -18x + -8x = 34 + 8x + -8x Combine like terms: -18x + -8x = -26x -18 + -26x = 34 + 8x + -8x Combine like terms: 8x + -8x = 0 -18 + -26x = 34 + 0 -18 + -26x = 34 Add '18' to each side of the equation. -18 + 18 + -26x = 34 + 18 Combine like terms: -18 + 18 = 0 0 + -26x = 34 + 18 -26x = 34 + 18 Combine like terms: 34 + 18 = 52 -26x = 52 Divide each side by '-26'. x = -2 Simplifying x = -2
| 5x+5=-3[x-1] | | -1-7(1-2k)=90 | | -7/2u+7/3=-2/3u-6 | | 4x+1=-2x+5 | | 5a-y=c | | -8(-5+3r)=112 | | 5(3x-6)-3=5(x-3)+2 | | 6z+10+2z-1=7z+14 | | m+15=2m | | -75/15 | | 7a+16=32+4a | | (3/5)(2x+8y) | | 2x+-7=3 | | 55+(x+110)=(165+2x) | | -(x-10)= | | 2.10+(0.80x)=11.70 | | -(5x+4)-4x=8+6x | | -2+10+(-3)+5= | | x^2-25x-150=0 | | s=27.13 | | 3p+4(2p-7)=-116 | | 6x-(3x)+x-6= | | -7x-5=-4-(7x-6) | | 1/3(x-9)=x+9 | | 6-6B-8B=8(-7+8B) | | 5m+6m=22 | | -n+7=-7(n+5) | | 1/9(27y+18)-9=-1/5(5y-45) | | 7a=16+4a | | 2x+x+12=92 | | u(v+9)+w(v-6)=z(v-1) | | 40+q=20 |